TECHNICAL AND TACTICAL ANALYSIS OF THE GAME OF QUALIFIED HANDBALL PLAYERS IN COMPETITION CONDITIONS - XALIKOVA Liliya Sagdullayevna («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article is devoted to identifying the key factors that determine the eﬀectiveness of technical and tactical actions and sports achievements of handball players. Analysis of competitive activity allowed us to establish a number of signifcant aspects that have a direct impact on the quality of execution of game elements and the overall sports result. Observations have shown that throws of the ball are mainly performed in the jump phase, while throws from a static position are extremely rare. The conducted studies have revealed the main error in passing the ball, which consists in reducing accuracy with active resistance from the defending opponents. Shortcomings in the technique of performing deceptive movements ("feints") lead to a decrease in the eﬀectiveness of individual game episodes. A positive correlation has been established between the high level of speed-strength preparedness of players and the improvement of not only physical ftness, but also technical capabilities, which contributes to the achievement of high sports results.